2018
DOI: 10.1186/s13018-018-0768-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lateral entry with crossed entry pinning for pediatric supracondylar humeral fractures: a meta-analysis

Abstract: BackgroundThe standard treatment for severe displaced pediatric supracondylar humeral fracture (SCHF) is closed reduction and percutaneous pin fixation. However, controversy persists concerning the optimal pin fixation technique. The purpose of this study was to compare the safety and efficacy on the configuration of lateral entry only with crossed entry pin fixation for SCHF, including Gartland type II and type III fractures in children.MethodsPublished literatures, including retrospective studies, prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 33 publications
(20 reference statements)
1
39
1
Order By: Relevance
“…Supracondylar humerus fractures are one of the most common elbow injuries in children 1,2 . The supracondylar region is at high risk of fracture due to thin structure between coronoid and olecranon fossae and predisposition to bending forces when falling on outstretched hand 1,3 . Cubitus varus is the most common complication, resulting from poor or loss of reduction 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Supracondylar humerus fractures are one of the most common elbow injuries in children 1,2 . The supracondylar region is at high risk of fracture due to thin structure between coronoid and olecranon fossae and predisposition to bending forces when falling on outstretched hand 1,3 . Cubitus varus is the most common complication, resulting from poor or loss of reduction 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that both crossed and lateral pinning configurations are comparable in terms of stiffness. However, because crossed pins are the most implicated in iatrogenic ulnar nerve injury, some of these studies have therefore advocated for lateral pinning alone as the preferred pinning technique for SHFs, as it offers comparable stability as crossed pins and has reduced or no risk of iatrogenic ulnar nerve injury [3, 69]. Loss of reduction is another theoretical complication of pinning fixation method which has been attributed to many factors [10, 11, 1518].…”
Section: Discussionmentioning
confidence: 99%
“…Lateral entry pinning is however preferred by many surgeons because it can achieve sufficient stability while eliminating the risk of ulnar nerve injury [69]. The configuration of the pins should be in accordance with the fracture line to achieve the best stability.…”
Section: Introductionmentioning
confidence: 99%
“…The non-dominant arm of boys aged five to seven years is most frequently involved. Extension type supracondylar fractures are the most frequent (99%) fracture type [1]. The mechanism of injury is secondary to a fall onto an outstretched hand [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Provided that adequate reduction has been obtained, Gartland I and II-type fractures are usually stabilized by nonsurgical means while Gartland III fractures are almost routinely treated by closed reduction and percutaneous pinning (CRPP) [2][3][4]. In 20% of the cases, open reduction may be necessary to obtain an acceptable result [1]. However, it seems that the displaced extension type supracondylar fractures of the pediatric elbow, collectively described as Gartland III-type fractures, are not a homogenous group.…”
Section: Introductionmentioning
confidence: 99%